Acute Cytomegalovirus infection as a cause of venous thromboembolism - Raffaella Lissandrin; Francesco Mojoli; Fausto Baldanti; Enrico Brunetti; Michela Pascarella; Maria Teresa Giordani; Francesca Rinaldi (Mediterranean Journal of Hematology and Infectious Diseases)
Acute Human Cytomegalovirus (HCMV) Infection  is an unusual cause of venous thromboembolism, a potentially life-threatening condition. Thrombus formation can occur at the onset of the disease or later during recovery and may also occur in the absence of acute HCMV hepatitis. It is likely due to both vascular endothelium damage caused by HCMV and impairment of the clotting balance caused by the virus itself. Here we report on two immunocompetent women with splanchnic thrombosis that occurred during the course of acute HCMV infection. Although the prevalence of venous thrombosis in patients with acute HCMV infection is unknown, physicians should be aware of its occurrence, particularly in immune-competent patients presenting with fever and unexplained abdominal pain referred to the splanchnic region.